Olfactory-colour crossmodal correspondences in art, science, and design - Spence, CJ (Springer, 2020)
The last few years have seen a rapid growth of interest amongst researchers in the crossmodal correspondences. One of the correspondences that has long intrigued artists is the putative association between colours and odours. While traditionally conceptualised in terms of synaesthesia, over the last quarter century or so, at least 20 published peer-reviewed articles have assessed the consistent, and non-random, nature of the colours that people intuitively associate with specific (both familiar and unfamiliar) odours in a non-food context. Having demonstrated such consistent mappings amongst the general (i.e. non-synaesthetic) population, researchers have now started to investigate whether they are shared cross-culturally, and to document their developmental acquisition. Over the years, several different explanations have been put forward by researchers for the existence of crossmodal correspondences, including the statistical, semantic, structural, and emotional-mediation accounts. While several of these approaches would appear to have some explanatory validity as far as the odour-colour correspondences are concerned, contemporary researchers have focussed on learned associations as the dominant explanatory framework. The nature of the colour-odour associations that have been reported to date appear to depend on the familiarity of the odour and the ease of source naming, and hence the kind of association/representation that is accessed. While the bidirectionality of odour-colour correspondences has not yet been rigorously assessed, many designers are nevertheless already starting to build on odour-colour crossmodal correspondences in their packaging/labelling/branding work.